Preparation, Physico-Chemical Properties and Biomedical Applications of Nanoparticles - Cavalu, Simona (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Nowadays, the impact of nanotechnology on applications in medicine and biomedical sciences has broader societal and economic effects, enhancing awareness of the business, regulatory, and administrative aspects of medical applications. The selected papers included in the present Special Issue gives readers a critical, balanced and realistic evaluation of existing nanomedicine developments and future prospects, allowing practitioners to plan and make decisions.The topics of this book covers the use of nanoparticles and nanotechnology in medical applications including biomaterials for tissue regeneration, diagnosis and monitoring, surgery, prosthetics, drug delivery systems, nanocarriers, and wound dressing. I would like to express my gratitude to all contributors to this issue, who have given so much of their time and effort to help create this collection of high quality papers.